Application of Lamport Digital Signature Scheme into the station-to-station protocol / Md Nizam Udin … [et al.] - Udin, Md Nizam; Mohd Amin, Farah Azaliney; Mat Abu, Nor Ainaa; Mohamad Sarif, Siti Nurfazlina; Mohammad Zuki, Nur Athirah (Universiti Teknologi MARA, 2022)
In cryptography, the key exchange protocol is very important before starting secure communication. Both parties will use an asymmetric key algorithm to exchange their keys for encryption and decryption. One of the methods to securely exchange the keys is Diffie-Hellman Key Exchange (DHKE) protocol. DHKE allows both parties to exchange their keys over the insecure public channel safely. However, DHKE protocol does not authenticate the message, making it easily exposed to third-party interruptions like Man-in-the-Middle (MitM) attack. Therefore, Station to Station (STS) protocols was introduced after modifying the DHKE protocol and adding authentication elements. Thus, this paper proposes to provide the authentication of the STS protocol by using Lamport Digital Signature Scheme. Lamport Digital Signature Scheme, also known as Lamport one-time signature scheme, gives very strong security because it can be built from any cryptographically secure one-way function and usually uses a cryptographic hash function. The results from the study are STS protocol algorithms that provide a verification scheme using the Lamport Digital Signature Scheme. As a result, both parties will obtain a common key for encryption and decryption, in which both parties play a role by using their respective digital signature for verification within the STS of this protocol.